2007
DOI: 10.1111/j.1462-5822.2007.00979.x
|View full text |Cite
|
Sign up to set email alerts
|

The proteins secreted by Trichomonas vaginalis and vaginal epithelial cell response to secreted and episomally expressed AP65

Abstract: SummaryWe showed recently that contact of human vaginal epithelial cells (VECs) by Trichomonas vaginalis and incubation with trichomonad proteins in conditioned medium induced expression of VEC genes. We performed 2-D SDS-PAGE followed by MALDI-TOF to identify the major secreted proteins. Based on protein abundance and separation of spots in 2-D gels, 32 major secreted proteins were examined, which gave 19 proteins with accession numbers. These proteins included known secreted cysteine proteinases. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 59 publications
2
60
1
Order By: Relevance
“…We showed earlier that brief contact of trichomonads with VECs produced dramatic changes in parasite morphology (9) in addition to synthesis of adhesins and other trichomonad proteins (26), suggesting host-specific signaling of parasites. More recently, we showed that parasite contact with VECs (24) and the released proteins of T. vaginalis (27), the majority of which were metabolic enzymes, including tv-ENO1, induced expression of numerous VEC genes. We now confirm that T. vaginalis tv-ENO1 is released and at the same time is present on the parasite surface.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We showed earlier that brief contact of trichomonads with VECs produced dramatic changes in parasite morphology (9) in addition to synthesis of adhesins and other trichomonad proteins (26), suggesting host-specific signaling of parasites. More recently, we showed that parasite contact with VECs (24) and the released proteins of T. vaginalis (27), the majority of which were metabolic enzymes, including tv-ENO1, induced expression of numerous VEC genes. We now confirm that T. vaginalis tv-ENO1 is released and at the same time is present on the parasite surface.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that secretions of patients contain numerous trichomonad proteins, including high-molecular-weight immunogenic proteins (3) and cysteine proteinases (5). Further, it is known that numerous proteins are readily released during growth, and multiplication without lysis of organisms has been established (2,27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differentially expressed protein spots in the amoeboid stage compared with the trophozoite stage are marked by arrows and protein spot numbers. tively, it is conceivable that, if secreted by the parasite, as has been found for numerous other proteins (43), this insulin-like GF may influence the host cell. Of interest in the future will be whether host hormones signal for trichomonal growth and multiplication.…”
Section: Fig 3 2-de Maps Of Trophozoites and Fn-bound Amoeboid Cells mentioning
confidence: 99%
“…Although in the literature it is routinely reported that men infected by their partners resolve their infections, there is neither experimental evidence nor clinical studies proving this. Reports have shown the expression of numerous virulence factors that permit this ancient protist to survive in the changing host environment of the female urogenital region (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Iron is an important modulator of upregulation and downregulation of the expression of virulence genes (8,(19)(20)(21)(22)(23)(24)(25).…”
mentioning
confidence: 99%